Molybdenum (VI)‐oxo Clusters Incorporation Activates g‐C3N4 with Simultaneously Regulating Charge Transfer and Reaction Centers for Boosting Photocatalytic Performance. (7th July 2022) - Zhang, Sai; Liu, Yang; Ma, Ran; Jia, Dashuang; Wen, Tao; Ai, Yuejie; Zhao, Guixia; Fang, Fang; Hu, Baowei; Wang, Xiangke
Abstract: Establishing local built‐in electric field of 2D semiconductors is one of the promising strategies to regulate the oriented charge delivery to active centers for enhancing photocatalytic performance. Herein, a novel heptamolybdate polyanions‐intercalated porous g‐C3 N4 ([Mo7 O24 ] 6− ‐ p CN) catalyst with integrating highly desirable visible‐light photocatalytic features is reported. After intercalation, the apparent reaction rate constants ( k app ) of [Mo7 O24 ] 6− ‐ p CN for bisphenol A (BPA) and 4‐chlorophenol (4‐CP) photodegradation are remarkably enhanced, which are 9.0 and 6.4 times faster than those of p CN, respectively. Analogously, the k app values of [Mo7 O24 ] 6– ‐CN for BPA and 4‐CP removal are also improved by contrast with CN. The experimental results and density functional theory calculations indicate that a local built‐in electric field is formed in [Mo7 O24 ] 6− ‐ p CN with a polarization direction from aromatic rings of g‐C3 N4 to the inserted [Mo7 O24 ] 6− clusters. Driven by the electric field, photogenerated carriers can be efficiently separated for better reactive oxidative species (ROSs) production. These O atoms are also proved as adsorption sites for phenols, greatly reducing the migration distance of ROSs and thus improving photocatalytic performances. This work offers a reliable strategy to construct local built‐in electric field via polyoxometalates intercalation for effective solar energy conversion and phenolic wastewater remediation. Abstract : 2D porous g‐C3 N4 with heptamolybdate ([Mo7 O24 ] 6− ) clusters intercalation achieve the efficient removal of refractory phenols from wastewater via visible‐light photodegradation. The inserted [Mo7 O24 ] 6− clusters induce the formation of local built‐in electric field, and drive fast charge transfer from conjugated aromatic ring to O atoms, while rich O sites are provided to adsorb phenols, thus improving the photocatalytic performances.